Pemahaman Keagamaan Guru Pendidikan Agama Islam DKI Jakarta - Taufik Abdillah Syukur (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2020)
The purpose of this study was to determine the religious understanding of Islamic religious education teachers in DKI Jakarta. This study used a descriptive qualitative method. The conclusion of this study showed that the majority of Islamic Religious Education teachers in DKI Jakarta had a contextual understanding of religion. The implication is that they still make reasoning and ratio the dominant tool in understanding Islam so it is hoped that they will always pay attention to the conditions and situations in which Islam is developed.